2021
DOI: 10.1007/s00417-021-05156-6
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix complexity of idiopathic epiretinal membranes and the bilaminar arrangement of the associated internal limiting membrane in the posterior retina

Abstract: Purpose To study the composition of the internal limiting membrane (ILM) of the retina, the extracellular matrix (ECM) of idiopathic epiretinal membranes (iERMs), and the relationships occurring between the two membranes. Methods Forty-six iERMs, 24 of them associated with the ILM, were collected and included in this study. The investigation has been carried out by immunofluorescence and confocal microscopy on glutaraldehyde- and osmium-fixed epon-embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Collagen IV is a constant constituent of iERMs [ 12 , 18 , 19 , 20 , 27 ], as well as of ERMs from PVR eyes [ 22 , 23 , 35 ]. A diffuse and considerable intense staining, which does not fit with a mere basement membrane-related immunoreactivity, has been reported by many investigators [ 12 , 19 , 20 , 21 , 27 ]. A study of collagen IV distribution in iERMs has been recently carried out by confocal microscopy showing that this collagen is deposited interstitially, intermingled with collagen I, with a staining intensity that progressively increases towards the vitreous side of the membrane.…”
Section: Ecm Components Of Iermsmentioning
confidence: 85%
See 4 more Smart Citations
“…Collagen IV is a constant constituent of iERMs [ 12 , 18 , 19 , 20 , 27 ], as well as of ERMs from PVR eyes [ 22 , 23 , 35 ]. A diffuse and considerable intense staining, which does not fit with a mere basement membrane-related immunoreactivity, has been reported by many investigators [ 12 , 19 , 20 , 21 , 27 ]. A study of collagen IV distribution in iERMs has been recently carried out by confocal microscopy showing that this collagen is deposited interstitially, intermingled with collagen I, with a staining intensity that progressively increases towards the vitreous side of the membrane.…”
Section: Ecm Components Of Iermsmentioning
confidence: 85%
“…Collagen I has been repetitively reported in iERMs [ 12 , 18 , 19 , 20 , 21 ], and it is certainly shared with other types of ERMs [ 22 , 23 , 24 ]. As collagen I is a hallmark of all fibrotic responses, one might expect to find it in all ERMs, and this was the case in many studies [ 12 , 20 , 21 ]. However, some investigators also observed a certain number of iERMs apparently lacking collagen I [ 18 , 19 ].…”
Section: Ecm Components Of Iermsmentioning
confidence: 99%
See 3 more Smart Citations